Use of passive sampling and high resolution mass spectrometry using a suspect screening approach to characterise emerging pollutants in contaminated groundwater and runoff - Pinasseau, Lucie; Wiest, Laure; Fildier, Aurélie; Volatier, Laurence; Fones, Gary R.; Mills, Graham A.; Mermillod-Blondin, Florian; Vulliet, Emmanuelle (The Science of the total environment, 2019)
Groundwater systems are being increasingly used to provide potable and other water supplies. Due to human activities, a range of organic pollutants is often detected in groundwater. One source of groundwater contamination is via stormwater infiltration basins, however, there is little information on the types of compounds present in these collection systems and their influence on the underlying groundwater. We developed an analytical strategy based on the use of passive sampling combined with liquid chromatography/high resolution quadrupole-time-of-flight mass spectrometry for screening for the presence of pesticide and pharmaceutical compounds in groundwater and stormwater runoff. Empore™ disk-based passive samplers (SDB-RPS and SDB-XC sorbents) were exposed, using for the first time a new specially designed deployment rig, for 10 days during a rainfall event in five different stormwater infiltration systems around Lyon, France. Stormwater runoff and groundwater (via a well, upstream and downstream of each basin) was sampled. Exposed Empore™ disks were solvent extracted (acetone and methanol) and the extracts analysed using a specific suspect compound screening workflow. High resolution mass spectrometry coupled with a suspect screening approach was found to be a useful tool as it allows a more comprehensive analysis than with targeted screening whilst being less time consuming than non-targeted screening. Using this analytical approach, 101 suspect compounds were tentatively identified, with 40 of this set being subsequently confirmed. The chemicals detected included fungicides, herbicides, insecticides, indicators of human activity, antibiotics, antiepileptics, antihypertensive and non-steroidal anti-inflammatory drugs as well as their metabolites. Polar pesticides were mainly detected in groundwater and pharmaceuticals were more frequently found in runoff. In terms of detection frequency of the pollutants, groundwater impacted by infiltration was found not to be significantly more contaminated than non-impacted groundwater. [Display omitted] •A novel Empore™ disk-based passive sampler for groundwater monitoring•Novel passive sampler used to monitor waters from infiltration systems•Passive sampler joined with LC-HRMS for groundwater and stormwater runoff screening•A rapid and comprehensive analysis based on a suspect screening workflow•Qualitative screening of polar pesticides and pharmaceuticals in groundwaters